Effect of feeding fish meal on milk production and its composition in dairy cows - YAZDANI, A R (The Indian Journal of Animal Sciences, 2011)
An experiment was conducted to evaluate the different levels of the feed ration of milking cows on milk production and its composition. The research was carried out in Gorgan city vicinity on lactating dairy cows (12), which were similar in number of calving and other parameters in a randomized complete design with 4 rations. The fish meal levels 0, 1, 2 and 3% (on the dry matter basis). Average daily milk yield were 21.30, 22.50, 22.48 and 23.12 kg/day for all the diets respectively, which all the diets were greater than control groups. Fat percentage and fat content of milk also were not affected by the diets composition.Body weight gain (g/d) of treatment 4 and 3 were significant over treatment 1 and 2. Dry matter intake for milk yield (kg/d) in treatment 1 was slightly higher than the other treatments (P<0.05). In the same way fat, protein and lactose percentage of different treatments were almost similar to each other, but no others significant effects were observed.